Research of the base conditions in the families with the phenomenon of co-addiction - Zhanserikova D. A., Tulebaeva A. B. (Interactive science, 2016)
the article addresses the problem of co-dependence, namely, the psychological state of the family with co-dependence in the frame of different approaches. Also, the authors explain the results of research that was aimed at studying the base conditions in the families with the phenomena of addictive behaviors. The results of current research can be used for development of effective psychological assistance in the families that have problems connected with alcoholism and drug addiction.
Keywords: Семья; наркомания; алкоголизм; психоактивные вещества; аддиктивное поведение; созависимость; аддикция; family; conditions; типовое семейное состояние; addictive behavior; psychoactive substance; addiction; co-addiction; base family; alcoholism; narcotic addiction; drug abuse